Efficacy and safety of doravirine/lamivudine/tenofovir disoproxil fumarate in HIV treatment: a real-world single-center study in China - Li, Aixin; Liu, Letian; Zhang, Hongwei; Wang, Xi; Li, Zaicun; Liu, An; Dai, Lili; Zhang, Jingji; Gao, Yue; Ye, Jiangzhu; Li, Jianwei; Sun, Lijun (Frontiers in Medicine, 2025)
BackgroundThe single-tablet regimen Doravirine/Lamivudine/Tenofovir Disoproxil Fumarate (DOR/3TC/TDF) has been included in international guidelines and recommendations and was approved by China’s National Medical Products Administration (NMPA) in early 2021 for adult human immunodeficiency virus (HIV)-1 infections. This study presents real-world results of a retrospective analysis of patients who initiated DOR/3TC/TDF at a Chinese HIV center.MethodsThis retrospective analysis was carried out on patients who received DOR/3TC/TDF (initial or switch) at the outpatient clinic of the Infection Center in Beijing Youan Hospital in China. Patients’ baseline characteristics, reasons for switching to DOR/3TC/TDF, along with the preliminary clinical, laboratory – based efficacy, safety, and tolerability data, were collected. All evaluations were in strict accordance with the protocols of our center. The statistical analysis was mainly descriptive, aiming to assess the changes in laboratory parameters from the baseline to the data – collection deadline, which was December 31, 2024.ResultFrom May 16 to October 29, 2024, 205 patients were prescribed DOR/3TC/TDF, either as an initiation or a switch. The cohort consisted mainly of males (96.1%), with a median age of 36.0 (31.0, 41.0) years. By the analysis deadline, the entire group had used DOR/3TC/TDF for 149.0 (90.0, 202.0) days. Among them, 40 patients were treatment-naïve, with a median HIV-1 ribonucleic acid (HIV-1 RNA) of 4.1 (3.7, 4.6) log10 copies/mL. At weeks 12 and 24, 64.5% [95% confidence interval (CI): 45.4, 80.8%] and 91.3% (95% CI: 72.0, 98.9%) of the participants achieved HIV-1 RNA < 50 copies/mL. Subgroup analysis showed that high viral load (VL) (≥105 copies/mL) and low CD4 counts (< 200 cells/μL) at baseline did not affect virological efficacy. The results of immune reconstitution were also satisfactory, with CD4 counts increased from 350 (264, 465) cells/μL at baseline to 541.0 (415.8, 789.5) cells/μL by the end of the follow-up (p > 0.05). 165 patients (80.5%) had treatment experience, and the most common cause for switching was treatment simplification (40%). After the switch, an equally high proportion of patients [97.6% (95% CI: 93.7, 99.3%) vs. 96.4% (95% CI: 92.2, 98.7%)] achieved HIV-1 RNA undetectable or <50 copies/mL (p > 0.05). Compared to baseline, there were no significant changes in liver enzymes and renal function (p > 0.05), while body weight, random blood glucose and blood lipid levels decreased significantly (p < 0.05). Among patients with central nervous system (CNS) symptom, both the Pittsburgh Sleep Quality Index (PSQI) and the Hospital Anxiety and Depression Scale (HADS) scores, as well as the proportion of patients with scores greater than 7 points, decreased significantly post-switch (p < 0.05).ConclusionWe provided an observational report on the effectiveness and safety of the short-term use of DOR/3TC/TDF in routine clinical practice.